Learning dynamics between cultural mediators in humanitarian healthcare: A case study - Maura Radicioni; Lucia Ruiz Rosendo (JoSTrans: The Journal of Specialised Translation)
This contribution explores the nature of the learning and learning relationships that have emerged between cultural mediators who have been working for the Italian NGO Emergency ONG Onlus at its Castel Volturno outpatient clinic since 2015. The contribution is part of an ongoing qualitative research study based on semi-structured interviews and ethnographic observations. By drawing on Engeström's (1987) theory of expansive learning and Lave and Wenger's (1991) theory of situated learning, the article questions traditional approaches to learning and notions of what constitutes an appropriate learning environment in this context. The findings show that the cultural mediators forge a community of practice that helps them construct and implement a new learning concept for their collective activity through learning by doing. This community of practice is pivotal for the work of the organisation as a whole, as it makes extensive use of languages and cultural mediation to provide guidance and mutual assistance and to contribute to the overall attainment of the organisation's humanitarian goals.